Art and homosexuality : a history of ideas - Reed, Christopher, 1961- (Oxford University Press, 2011)
"This bold, globe-spanning survey is the first book to thoroughly explore the radical, long-standing interdependence between art and homosexuality. It draws examples from the full range of the Western tradition, including classical, Renaissance, and contemporary art, with special focus on the modern era. It was in the modern period, when arguments about homosexuality and the avant-garde were especially public, that our current conception of the artist and the homosexual began to take shape, and almost as quickly to overlap. Not a chronology of gay or lesbian artists, the book is a fascinating and sophisticated account of the ways two conspicuous identities have fundamentally informed one another. Art and Homosexuality discusses many of modernism's canonical figures--painters like Courbet, Picasso, and Pollock; writers like Whitman and Stein--and issues, such as the rise of abstraction, the avant-garde's relationship to its patrons and the political exploitation of art. It shows that many of the core ideas that define modernism are nearly indecipherable without an understanding of the paired identities of artist and homosexual. Illustrated with over 175 b/w and color images that range from high to popular culture and from Ancient Greece to contemporary America, Art and Homosexuality punctures the platitudes surrounding discussions of both aesthetics and sexual identity and takes our understanding of each in stimulating new directions."--Publisher description